2015
DOI: 10.14304/surya.jpr.v3n2.2
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy-Based Sensing of Glycated Hemoglobin: Critical Analysis and Future Outlook

Abstract: Glycated hemoglobin is a clinically established important biomarker that provides retrospective value of blood glucose concentration over the preceding 2-3 months. Owing to the biochemical specificity and multiplexing capability, Raman spectroscopy has emerged as a promising tool for detection and quantification of blood constituents in a label-free and non-destructive manner. Here, we critically review the Raman spectroscopy-based approach to detect and quantify this important biomarker. The potential of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The first detection of HbA1c using surfaceenhanced resonance Raman spectroscopy was carried out in colloidal solutions [11]. Further studies have explored Raman spectroscopy to study HbA1c in vitro, using several enhancing techniques [12][13][14][15]. More recently, Villa-Manríquez et al have shown that Raman spectroscopy and principal component analysis combined with a support vector machine can classify qualitatively glycated hemoglobin levels in vivo [16].…”
mentioning
confidence: 99%
“…The first detection of HbA1c using surfaceenhanced resonance Raman spectroscopy was carried out in colloidal solutions [11]. Further studies have explored Raman spectroscopy to study HbA1c in vitro, using several enhancing techniques [12][13][14][15]. More recently, Villa-Manríquez et al have shown that Raman spectroscopy and principal component analysis combined with a support vector machine can classify qualitatively glycated hemoglobin levels in vivo [16].…”
mentioning
confidence: 99%
“…The scattering is mostly elastic (such as Rayleigh scattering and Mie scattering), with a very small percentage of inelastic including Raman scattering (stokes and anti-stokes). Elastic scattering produces light with the same frequency and wavelength as the incident light, while inelastic scattering generates light with multiple wavelengths and frequencies [99]. Most of the light that is scattered is elastic, and about one in every million scattered photons takes part in inelastic scattering [48,100].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Elevated levels of HbA1c has been indicated as a well-known biomarker for diabetes, and the HbA1c test provides an average blood sugar measurement of the past two to three months by measuring the percentage of blood sugar attached to hemoglobin. 33,34 A recent review has focused on the future outlook of using Raman spectroscopy for sensing HbA1c, 35 and one of the earlier papers to investigate Raman spectroscopy for detection of HbA1c was reported by Barman et al in 2012. 36 More recently, González-Viveros investigated various concentrations of commercial lyophilized HbA1c in distilled water.…”
Section: Monitoring Glycated Hemoglobin Levels For Indicating Diabetesmentioning
confidence: 99%